Synthesis, Crystal and Electronic Structures of New Narrow-Band-Gap Semiconducting Antimonide Oxides RESbO and RESb-δO, with RE = La, Sm, Gd, and Ho. - Peng Wang; Forbes, Scott; Kolodiazhnyi, Taras; Kosuda, Kosuke; Mozharivskyj, Yurij (Journal of the American Chemical Society, 2010)
In the search for high-temperature thermoelectric materials, two families of novel, narrow-band-gap semiconducting antimonide oxides with the compositions RESbO and RESb-δO (RE = La, Sm, Gd, Ho) have been discovered. Their synthesis was motivated by attempts to open a band gap in the semimetallic RESb binaries through a chemical fusion of RESb and corresponding insulating REO. Temperatures of 1350 °C or higher are required to obtain these phases. Both RESbO and RESb-δO adopt new monoclinic structures with the C2/m space group and feature similar REO frameworks composed of "REO" tetrahedral units. In both structures, the Sb atoms occupy the empty channels within the REO sublattice. High-purity bulk Sm and Ho samples were prepared and subjected to electrical resistivity measurements. Both the RESbO and RESb-δO (RE = Sm, Ho) phases exhibit a semiconductor-type electrical behavior. While a small band gap in RESbO results from the separation of the valence and conduction bands, a band gap in RESb-δO appears to result from the Anderson localization of electrons. The relationship among the composition, crystal structures, and electrical resistivity is analyzed using electronic structure calculations.